Involvement of Visceral Adipose Tissue in Immunological Modulation of Inflammatory Cascade in Preeclampsia - Katsuhiko Naruse; Juria Akasaka; Aiko Shigemitsu; Taihei Tsunemi; Natsuki Koike; Chiharu Yoshimoto; Hiroshi Kobayashi (Mediators of Inflammation)
Objectives. The pathophysiology of preeclampsia is characterized by abnormal placentation, an exaggerated inflammatory response, and generalized dysfunction of the maternal endothelium. We investigated the effects of preeclampsia serum on the expression of inflammation-related genes by adipose tissue. Materials and Methods. Visceral adipose tissue was obtained from the omentum of patients with early ovarian cancer without metastasis. Adipose tissue was incubated with sera obtained from either five women affected with severe preeclampsia or five women from control pregnant women at 37°C in a humidified incubator at 5% CO2 for 24 hours. 370 genes in total mRNA were analyzed with quantitative RT-PCR (Inflammatory Response & Autoimmunity gene set). Results. Gene expression analysis revealed changes in the expression levels of 30 genes in adipose tissue treated with preeclampsia sera. Some genes are related to immune response, oxidative stress, insulin resistance, and adipogenesis, which plays a central role in excessive systemic inflammatory response of preeclampsia. In contrast, other genes have shown beneficial effects in the regulation of Th2 predominance, antioxidative stress, and insulin sensitivity. Conclusion. In conclusion, visceral adipose tissue offers protection against inflammation, oxidative insults, and other forms of cellular stress that are central to the pathogenesis of preeclampsia.